What we know and don't know about the immunization program of Ethiopia: a scoping review of the literature - Binyam Tilahun; Zeleke Mekonnen; Alyssa Sharkey; Asm Shahabuddin; Marta Feletto; Meseret Zelalem; Kabir Sheikh (BMC, 2020)
Abstract Background There has been significant recent prioritization and investment in the immunization program in Ethiopia. However, coverage rates have stagnated and remained low for many years, suggesting the presence of systemic barriers to implementation. Hence, there is a need to consolidate the existing knowledge, in order to address them and consequently improve program effectiveness. Methods A thorough literature review and Delphi method were used. In this review, we searched Pubmed/Medline, WHO library, Science direct, Cochrane library, Google scholar and Google using different combinations of search strategies. Studies that applied any study design, data collection and analysis methods related to immunization program were included. In the Delphi method, a panel of 28 national and international experts were participated to identify current evidence gaps and set research priorities under the immunization program. Results In this review, a total of 55 studies and national documents were included. The review showed that the vaccination coverage ranged from 20.6% in Afar to 91.7% in Amhara region with large inequities related to socio-economic, health service access and knowledge about vaccination across different settings. Only one study reported evidence on timeliness of immunization as 60%. The review revealed that 80% of health facilities provide immunization service nationally while service availability was only 2% in private health facilities. This review indicated that poor vaccine storage, vaccine shortage, service interruptions, poor defaulter tracing, low community engagement and poor documentation were the main barriers for the Expanded Program on Immunization with variations across different regions. Through expert panel of discussion using Delphi method, 10 priority research areas were identified across different domains of the immunization program at national level. Conclusion We found out that there is substantial knowledge on vaccination coverage, however, there is little evidence on timeliness of vaccination. The existing barriers that affect full immunization coverage also varied from context to context which indicates there is a need to design and implement evidence based locally tailored interventions. This review also indicated evidence gaps with more focus on health system related implementation barriers at lower level and identified further research priorities in the immunization program of Ethiopia.